The effectiveness of taekwondo headgear in reducing impact force - Azam, Siti Hanisah Linggi Mohd (Universiti Sains Malaysia, 2015)
Taekwondo is categorized as a contact sports, it is rough and prone to injury. Kicking is the most used technique in the tournament. It can produce a very high impact force and causing an injury. Many prevention methods have been taken to reduce the risk of injury including wearing a headgear. Many still doubt about the effectiveness of headgear in reducing impact force. This study is conducted to improve the understanding about the properties of headgear in reducing impact force. The objective of the study is to examine the properties of a selected brand of taekwondo head gear in reducing impact force. A force platform is used to measure the impact force produced from releasing a medicine ball at different height. A force is measured without a headgear, with a new headgear and with a used headgear. Preliminary findings showed that using a headgear can reduce significant amount of impact force produced from a medicine ball. The result showed a significant amount of force reduction for a comparison between without headgear and with headgear for each of the tested area. The comparison between new and used showed a significant difference in the amount of force reduction for the big ear release and small ear release canal. It can be concluded that time is not affecting the frontal and occipital region of the headgear, but it is affecting the effectiveness of big ear-release canal and small ear-release canal. From this study, it can be concluded that there are internal properties of headgear in reducing impact force. It is effective in reducing impact force for a range of force applied.